THE USE OF TOOLS IN STRATEGIC MANAGEMENT FOR THE FORMATION OF THE INCREDIBLE GLASSES COMPANY'S DEVELOPMENT STRATEGY BASED - Elena Shatskaya; Karolina Kafyan; Irina Esaulova (Вестник Северо-Кавказского федерального университета)
This report concerns the interest of Incredible Glasses to enter the US market. This information, matched with Porter analyses, will be used to formulate and propose an entry strategy for Incredible Glasses in US. Data used in this research are based on a mix between primary and secondary sources. Secondary data were collected from Industry reports, books and other digital sources. This information was fundamental to perform a general analysis of the country and the industry, and to understand which the main market segments were. Primary sources were collected through interview with main actors of the market, such as opticians, distributors and other experts.